Deskripsi Gerak Tari Pirdi di Sanggar Seni Nusa Kirana - Wati, Sartila; Nurdin, Nurdin; Firmansyah, Dedy (ANTHOR: Education and Learning Journal, 2022)
The purpose of this research is to describe the movements of the Pirdi dance at the Nusa Kirana Art Studio, Palembang. The method used by researchers is the descriptive qualitative method. Data collection techniques for this study used observation, documentation, and interviews. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results obtained in this study are that the Pirdi dance is a dance from the city of Palembang which is categorized as a creative dance created in 1972 and has been performed in more than 27 countries from 1994 to 2002, this dance functions as entertainment. This dance tells about the life of the people of Palembang city, the number of dancers can be even or odd, it can be danced by females and male dancers, and it can also be female dancers. songket spans, 2) the prayer movement assembling the plate and 3) theprayer movement assembling the jug. Middle/ core movement, consisting of 1) deer jumping motion, 2) begelut squirrel movement, 3) repetition 4) deer jumping motion, 5) squirrel twisting motion, 6) gazing motion, 7) repetition of deer jumping.